PELATIHAN GOOGLE CLASSROOM PADA GURU SEKOLAH DASAR DI DESA BALONGGEMEK JOMBANG - Dedy Rahman Prehanto; Aries Dwi Indriyanti; Mochamad Arif Irfa’i (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2022)
mastery of skills in the field of Information Technology. The purpose of implementing Community Service activities which took place in Balonggemek Village, Jombang Regency is to provide training and assistance for Google classroom training for elementary school teachers so that learning for elementary school students is more interesting and fun. The partners of this community service are elementary school teachers in Balonggemek Village, Jombang Regency. The methods used are identifying partner problems, preparation of activities (compilation of materials, necessary equipment), determining training capacity, schedule and arrangement of training events, implementation of activities and evaluation of activity implementation. The google classroom training materials consist of the functions and uses of google classroom, accessing google classroom, adding students to the class, viewing the class assignment page, viewing user pages, creating assignments, providing input and grades. The implementation of the community service activities went well and smoothly. This can be seen from the enthusiasm of the participants in the training. The evaluation results of the level understanding of the participants in the training can be seen by comparing the pre-test and post-test score, which shows 45% and 92%, respectively.Keywords: google classroom training, primary school teachers, Balonggemek Village, Jombang RegencyAbstrak: Pembelajaran di masa pandemi Covid-19 yang memprioritaskan pembelajaran secara daring atau online membutuhkan penguasaan kemampuan di bidang Teknologi Informasi. Tujuan pelaksanaan kegiatan Pengabdian Kepada Masyarakat (PKM) yang mengambil lokasi di Desa Balonggemek Kabupaten Jombang adalah memberi pelatihan dan pendampingan pelatihan google classroom bagi guru-guru Sekolah Dasar agar pembelajaran kepada murid-murid Sekolah Dasar lebih menarik dan menyenangkan. Mitra kegiatan PKM adalah guru-guru Sekolah Dasar di Desa Balonggemek Kabupaten Jombang. Metode yang dilakukan adalah mengidentifikasi permasalahan mitra, persiapan kegiatan (penyusunan materi, perlengkapan yang diperlukan), menentukan kapasitas pelatihan, jadwal dan susunan acara pelatihan, pelaksanaan kegiatan serta evaluasi pelaksanaan kegiatan. Materi pelatihan google classroom terdiri dari fungsi dan kegunaan google classroom, mengakses google classroom, menambahkan siswa ke kelas, melihat halaman tugas kelas, melihat halaman pengguna, membuat tugas, memberikan masukan dan nilai. Kegiatan pelaksanaan Pengabdian Kepada Masyarakat (PKM) berlangsung baik dan lancar. Hal ini terlihat dari antusias para peserta dalam mengikuti pelatihan. Hasil evaluasi terhadap tingkat pemahaman peserta dalam mengikuti pelatihan terlihat dari hasil sebelum pelatihan (pre test) sebesar 45% dan sesudah pelatihan (post test) yang menunjukkan hasil 92%.Kata kunci: Pelatihan google classroom, guru Sekolah Dasar, Desa Balonggemek Kabupaten Jombang